Cardiac Progenitors Induced from Human Induced Pluripotent Stem Cells with Cardiogenic Small Molecule Effectively Regenerate Infarcted Hearts and Attenuate Fibrosis. Issue 6 (December 2018) - Xuan, Wanling; Wang, Yan; Tang, Yaoliang; Ali, Ailia; Hu, Hong; Maienschein-Cline, Mark; Ashraf, Muhammad
Abstract : ABSTRACT: Cardiac progenitor cells (CPCs) being multipotent offer a promising source for cardiac repair due to their ability to proliferate and multiply into cardiac lineage cells. Here, we explored a novel strategy for human CPCs generation from human induced pluripotent stem cells (hiPSCs) using a cardiogenic small molecule, isoxazole (ISX-9) and their ability to grow in the scar tissue for functional improvement in the infarcted myocardium. CPCs were induced from hiPSCs with ISX-9. CPCs were characterized by immunocytochemistry and RT-PCR. The CPC survival and differentiation in the infarcted hearts were determined by in vivo transplantation in immunodeficient mice following left anterior descending artery ligation and their effects were determined on fibrosis and functional improvement. ISX-9 simultaneously induced expression of cardiac transcription factors, NK2 homeobox 5, islet-1, GATA binding protein 4, myocyte enhancer factor-2 in hiPSCs within 3 days of treatment and successfully differentiated into three cardiac lineages in vitro . Messenger RNA and microRNA-sequencing results showed that ISX-9 targeted multiple cardiac differentiation, proliferation signaling pathways and upregulated myogenesis and cardiac hypertrophy related-microRNA. ISX-9 activated multiple pathways including transforming growth factor β induced epithelial–mesenchymal transition signaling, canonical, and non-canonical Wnt signaling at different stages of cardiac differentiation. CPCs transplantation promoted myoangiogenesis, attenuated fibrosis, and led to functional improvement in treated mice. Abstract : Supplemental Digital Content is available in the text